PERANAN MURSYID TAREKAT QODIRIYAH NAQSYABANDIYAH DALAM PEMBINAAN AKHLAK JEMAAHNYA DI SURYALAYA - Abdul Muis, Cecep; Yogi Adi Sucipto (HASBUNA : Jurnal Pendidikan Islam, 2023)
Tarekat as a path that must be taken by a sufi to get closer to Allah SWT. Is a method of moral pshychology to guide a person to know god, under the supervision of muravid al-thartgah. The tarekat has various names depending on the founder of the tarekat. One of them is Muhammad bin Muhammad Bahauddin Bukhari an-naksayabandiyah in the VII century hijriyah in Bukhara. Mursyid Tarekat Qodiriyah Naqsabandiyyah has an important role in coaching the congregation. As well as society. Mursyid is a mentor or leader who plays an active role in carrying out spiritual development and spiritual knowledge for the muslim community around him. In carrying out coaching there are several religious values contained in the taechings of the qodiriyah naqsayabandiyyah order such as the values of aqidah morals and syari’at aim to increase piety and awareness of Allah. The problem in the research is what is the role of the Mursyid of the qodiriiyah naqsabandiyah congregation in the developing the morals of the congregation in Suryalaya. As for the informants in this study, namely Das K.H Sandisi as the mursyid of the tarekat and Ustad Dadang as the coordinating head. Thos research is a type of qualitative research with a descriptive approach. The data collection technique are observation, interviews and documentation. Based on the results above, it can be concluded that the role of the Musyid of the qodiriyah naqsabandiyyah order in the moral development of the congregation in suryalaya is very important, because without a murshid, the teachings of the tarekat will not run smoothly and effectively.